English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

(2sqrt 7+6sqrt 11)(4sqrt 7-sqrt 11)
multiply i'm getting lost in the middle of the expression
i foil and then i get lost

2007-01-12 17:45:47 · 5 answers · asked by colecole1979 1 in Science & Mathematics Mathematics

5 answers

(2sqrt7 + 6sqrt11)*(4sqrt7 - sqrt11)
= (2sqrt7 * 4sqrt7) - (2sqrt7 * sqrt11) + (6sqrt11 * 4sqrt7) - (6sqrt11 * sqrt11)
= 56 - 2sqrt77 + 24sqrt77 - 66
= 22sqrt77 -10
ans = 22sqrt77 - 10

2007-01-12 18:08:12 · answer #1 · answered by som5enak 2 · 0 0

U can do it easily.
(2*sqrt 7+6*sqrt11)(4*sqrt 7-sqrt 11)
=2sqrt7(4*sqrt7-sqrt11)+6sqrt11(4sqrt7-sqrt 11)
We know that sqrt7*sqrt7=7
Threfore 8*7-2sqrt77+24sqrt77-6*11
=56+22sqrt77-66
= -10+22sqrt77

2007-01-13 03:59:54 · answer #2 · answered by tripleh_game_2006 2 · 0 0

f= 8*7= 56 (because 2*4*sqrt7*sqrt7)
o= -2*sqrt77 (-2*sqrt7*sqrt11)
i= 24*sqrt77 (6*4*sqrt7*sqrt11)
l= -66 (-6*sqrt11*sqrt11)

so you have 56 - 2 sqrt77 + 24sqrt77 - 66 =

56 - 22 sqrt 77 - 66

2007-01-13 01:54:11 · answer #3 · answered by Dipti 2 · 0 1

-10 + 22sqrt(77)

2007-01-13 02:02:04 · answer #4 · answered by ? 6 · 0 1

(2V7+6V11)(4V7-V11)

YOU ARE RIGHT, USE FOIL:

2V7 * 4V7 - 2V7*V11 + 6V11*4V7 -6V11*V11

8*7 -2V77 +24V77 -6*11

56 + 22V77 -66

22V77 -10

APPROX. 183.05

2007-01-13 02:00:56 · answer #5 · answered by Stryder 2 · 1 0

fedest.com, questions and answers